African primary care research: Participatory action research - Bob Mash (AOSIS, 2014)
This article is part of the series on African primary care research and focuses on participatory action research. The article gives an overview of the emancipatory-critical research paradigm, the key characteristics and different types of participatory action research. Following this it describes in detail the methodological issues involved in professional participatory action research and running a cooperative inquiry group. The article is intended to help students with writing their research proposal.